Pengaruh Kualitas Pelayanan, Citra Merek, Harga, dan Kualitas Produk Terhadap Loyalitas Pelanggan - Aditya Dwi Putra; Nurul Azizah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
One of the beverage products that has many fans in Indonesia is coffee. Coffee is one of Indonesia's leading plantation commodities that has an important role, especially as a source of foreign exchange, a provider of employment. Jokopi is one of the coffee shop brands that has a contemporary coffee drinking trend. With the tagline "telling and cultivating". The purpose of this study is to determine the effect of Brand Image, brand image, price and Service Quality simultaneously on customer loyalty. In this study, the research method used is a quantitative research method and in this study there are 30 to 500 samples, in addition, if the study will conduct an analysis with multivariate (correlation or multiple regression), then the number of sample members is at least 10 times the number of variables studied. The results of the test together (simultaneously) show that the variables of Service Quality, Brand Image, Price and Product Quality have an effect on Customer Loyalty, this can be proven by the results of F count 15.729 or a significance value of 0.000 <0.05.